Influence of land-use/land-cover change on landscape connectivity for an endemic threatened amphibian (Argenteohyla siemersi pederseni, Anura: Hylidae) - Schivo, Facundo Mauro (2020)
Context: Modifications in natural landcover generally result in a loss of habitat availability for wildlife and it’s persistence will depend largely on their spatial configuration and functional connections. Argenteohyla siemersi is a threatened and endemic amphibian whose habitat is composed of forest patches near rivers and water bodies edges. Objectives: This study aimed to analyse the accessible habitat for this species and identify key elements to maintain its ecological network in two different types of land uses: an anthropized area with extensive cattle raising and a protected area. Methods: The structural and functional characteristics of both landscapes were analyzed. The connectivity at landscape level and the contribution of each habitat patch were evaluated through simulation models with different dispersion distances in the context of the graph theory. Results: In both landscapes, nine types of landcover were identified with different compositions. Remarkable differences were found in habitat connectivity for this amphibian species between both landscapes. As the percentage of dispersion distance increases, reachable habitat increases as well, although with higher percentages in the protected area. Two corridors were identified in the protected landscape and one in the rangeland one; patches and key links constituted all of them. Conclusions: The present work provides spatially explicit results with a quantitative basis. It could be useful as a tool for the development of management plans aimed at guaranteeing the functionality of the ecological network for this endangered species and, therefore, contribute to its long-term conservation.